2016
DOI: 10.1002/mnfr.201500899
|View full text |Cite
|
Sign up to set email alerts
|

Rhubarb extract prevents hepatic inflammation induced by acute alcohol intake, an effect related to the modulation of the gut microbiota

Abstract: These findings suggest that some bacterial genders involved in gut barrier function, are promoted by phytochemicals present in rhubarb extract, and could therefore be involved in the modulation of the susceptibility to hepatic diseases linked to acute alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
110
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(123 citation statements)
references
References 57 publications
12
110
0
1
Order By: Relevance
“…Alcohol disrupts the intestinal microbiome, alters the intestinal barrier and might affect various other intestinal functions such as mucosal immunity. Therapies such as various diets, prebiotics and probiotics might have the potential to influence and correct these disturbances and appear as potential future therapies for these diseases 60. In addition, manipulation of the gut microbiota by prebiotics/probiotics or FMT selectively targeting key pathobionts might reflect another promising treatment strategy.…”
Section: Alcoholic Liver Disease and Microbiotamentioning
confidence: 99%
“…Alcohol disrupts the intestinal microbiome, alters the intestinal barrier and might affect various other intestinal functions such as mucosal immunity. Therapies such as various diets, prebiotics and probiotics might have the potential to influence and correct these disturbances and appear as potential future therapies for these diseases 60. In addition, manipulation of the gut microbiota by prebiotics/probiotics or FMT selectively targeting key pathobionts might reflect another promising treatment strategy.…”
Section: Alcoholic Liver Disease and Microbiotamentioning
confidence: 99%
“…Rhubarb mainly contains anthraquinone derivatives which have been reported with anticancer and hepatoprotective activities (Huang et al, 2007; Zhao, Wang, Zhou, Shan, & Xiao, 2009). A recent paper however showed that Rhubarb extract modified gut microbiota of a standard diet (AIN93M)-fed DIO mice (Neyrinck et al, 2016). Supplementation of Rhubarb extract (0.3% in a standard AIN93M diet for 17 days) increased the relative abundance of A. muciniphila to 38.9% of fecal total bacteria (measured by pyrosequencing of 16sRNA gene) in DIO mice (12-wk-old) mice (as compared to 9.4% for mice on the standard diet only).…”
Section: Rhubarb Extract Promoted a Muciniphila Abundancementioning
confidence: 99%
“…The increase was very remarkable considering the treatment only lasted for 17 days. Coincidentally, the relative abundance of Firmicutes was reduced to 24.1% (from 48.7% in control mice) (Neyrinck et al, 2016). Rhubarb extract also improved intestinal homeostasis and alcohol-induced oxidative stress and inflammation in the liver (Neyrinck et al, 2016).…”
Section: Rhubarb Extract Promoted a Muciniphila Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…Lactobacillus fermentum HY01 strain in some studies showed that had significant preventive effects in dextran sulfate sodium induced-colitis; at the same time, it can efficiently reduce edema, inflammatory cells infiltration, and colon mucosa injury. In addition to play a significant function in the down-regulation of concentrations of pro-inflammatory factors (IFN-, IL-12, TNF, and IL-6) in particular shows a hopeful prevention for I_B_ degradation, decreases the protein levels of iNOS and COX-2 along with inhibition of NF-_B p65 phosphorylation cascades [17,96,97]. The outcome from some studies obtained from Lactobacillus rhamnosus GG, Lactobacillus rhamnosus KLSD, Lactobacillus helveticus IMAU70129, and Lactobacillus casei IMAU60214 demonstrated that strains induced early proinflammatory cytokines for example IL-8, TNF-α, IL-12p70, IL-6 and IL-1β.…”
Section: Enhancement Of Anti-inflammatory Responsementioning
confidence: 99%